Psikososialitas dalam Teori Freud Merunut Kontribusi dan Kontroversi Sang Bapak Psikoanalisis dalam Studi Manusia - Pradnya Paramitha, Putu Elvira; Perdana, Indra; Bungai, Joni (Metta : Jurnal Ilmu Multidisiplin, 2025)
The theory of psychoanalysis developed by Sigmund Freud is one of the most influential contributions in the history of modern psychology. This research discusses the role of Sigmund Freud's concepts of psychosociality in understanding individual dynamics in contemporary psychology. This research method adopts a qualitative research design. As for this research, it is accompanied by a library approach. This approach was chosen to explore and analyze Sigmund Freud's psychoanalytic theories through relevant library sources, such as books, journal articles and Freud's primary sources. Through an analysis of the literature, Freud's contribution to the understanding of personality structure, the concept of libido, and self-defense mechanisms is explained. The data collection technique in this research was carried out through a literature review. The data analysis technique uses the Miles and Huberman model, which is a systematic approach to analyzing qualitative data. Data analysis according to the Miles and Huberman approach is a systematic process for understanding and interpreting data in a study. The findings of this research highlight the relevance of Freud's concepts in modern therapeutic approaches and understanding of human behavior. Suggestions for the development of integrative therapeutic approaches, comparative studies between Freudian and alternative theories, and policy implications for psychological education are also discussed.